The Pengaruh Komposisi Unsur Gadolinium (Gd) terhadap Magnesium (Mg) Melalui Casting sebagai Bahan Dasar Implan: Kajian Literatur - Susanti, Oknovia; Affi, Jon; Asrilia, Yuni (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2020)
Magnesium has potential as an implant base material because of its properties required by human bones, such as biocompatibility, non-toxic and easily dissolved (degradability). This element is needed by the human body as much as 375 Mg / day which is stored in bone and blood tissue. Magnesium is the lightest metal which has a mass type of 1.738 gr / cm3 with a modulus of elasticity of 42 GPa which is very close to the modulus of elasticity of natural human bones 10-40 GPa and can be degraded through corrosion that occurs in body fluids containing 0.9 wt% chloride. . Pure magnesium has a high corrosion rate, so there is no need to add alloying elements which can reduce the corrosion rate and at the same time improve its mechanical properties. One of them is through the addition of rare earth alloy elements, namely gadolinium. Currently, magnesium and gadolinium alloys as biodegradable materials are mostly made by casting methods. Therefore, it is necessary to make a literature review on alloys of magnesium and gadolinium by casting methods to see the effect of adding the element gadolinium to magnesium alloys suitable for bone implants in the human body. Based on the results of a literature review of the composition of the effect of the element gadolinium (Gd) on magnesium (Mg) alloys in the casting process for implant base materials, it can be seen that the addition of Gd more than 10% will increase the mechanical properties of the Mg-Gd alloy and a composition suitable for biodegradable implants can be adjusted depending on the needs and health standards as an implant. This Mg-Gd alloy has a wide range of TYS and UTS with TYS 33 MPa-200 MPa and UTS 78 MPa-250 MPa. And the more the element gadolinium is added to magnesium, the smaller the grain size. The smaller the grain size will increase the strength and hardness of the Mg-Gd alloy. Key Words: Biodegradable implants, Pengecoran, Magnesium alloy, Unsur tanah jarang